1989
DOI: 10.1017/s0022029900028806
|View full text |Cite
|
Sign up to set email alerts
|

Biologically active casein peptides implicated in immunomodulation

Abstract: Maternal milk should not only be considered as a nutrient, but also as a protecting agent against aggressions from the neonate's new environment. Breastfeeding facilitates transmission of a passive immunity by multifunctional factors which have a direct effect on the neonate's resistance to bacterial and viral infections. Among these factors are the main milk proteins, the caseins: during enzymic digestion of human and bovine caseins, immunomodulating peptides are released. Corresponding synthetic peptides sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(78 citation statements)
references
References 20 publications
4
72
0
2
Order By: Relevance
“…It was demonstrated that peptides from α s1 -casein (residues 194-199 and 23-34) and β-casein (residues 63-68 and 191-193) stimulate phagocytosis by murine peritoneal macrophages and consequently exert a protective effect against Klebsiella pneumoniae infection in mice aft er intravenous treatment (25,(27)(28)(29)(30)(31). The peptide α s1 -casein (residues 23-34) was demonstrated to be produced in Parmigiano Reggiano during ripening (19).…”
Section: Immunomodulatory Peptidesmentioning
confidence: 99%
“…It was demonstrated that peptides from α s1 -casein (residues 194-199 and 23-34) and β-casein (residues 63-68 and 191-193) stimulate phagocytosis by murine peritoneal macrophages and consequently exert a protective effect against Klebsiella pneumoniae infection in mice aft er intravenous treatment (25,(27)(28)(29)(30)(31). The peptide α s1 -casein (residues 23-34) was demonstrated to be produced in Parmigiano Reggiano during ripening (19).…”
Section: Immunomodulatory Peptidesmentioning
confidence: 99%
“…the size of active sequences may vary from two to twenty amino acid residues, and many peptides are known to have multifunctional properties (27) e.g., peptides from the sequence 60-70 of β-casein show immunostimulatory, opioid and ACE-inhibitory activities. This sequence has been defined as a strategic zone (26,28). The sequence is protected from proteolysis because of its high hydrophobicity and the presence of proline residues.…”
Section: Occurrence Of Bioactive Peptides In Dairy Productsmentioning
confidence: 99%
“…Casein phosphopeptides from fermented milk products, such as plain yogurts and cheeses, has shown beneficial effects on the immune system including the mitogenic effect and IgA enhancing effect in mouse spleen cell cultures [3]. According to the results of other studies, human -casein fraction 54-59 has demonstrated to enhance the phagocytic activity of macrophages both in mice and humans and increase resistance against certain bacteria in mice [6,149].…”
Section: Table 3 Milk Proteins-derived Peptides With Antiviral and Imentioning
confidence: 99%
“…Peptides from casein [4,6,142], -lactoglobulin [143,144], and -lactalbumin [7] also enhance and/or suppress immune cell function (Table 3). Note: ACE-inhibition, Angiotensin-converting enzyme-inhibition.…”
Section: Milk Derived Peptides As Immune Modulatorsmentioning
confidence: 99%
See 1 more Smart Citation